GeSn p-i-n detectors integrated on Si with up to 4% Sn - Oehme, Michael; Schmid, M.; Kaschel, M.; Gollhofer, M.; Widmann, D.; Kasper, E.; Schulze, J. (Applied Physics Letters, 2012)
GeSn heterojunction photodetectors on Si substrates were grown with Sn concentration up to 4%, fabricated for vertical light incidence, and characterized. The complete layer structure was grown by means of ultra low temperature (100 °C) molecular beam epitaxy. The Sn content shifts the responsivity into the infrared, about 310 nm for the 4% Sn sample. An increase of the optical responsivity for wavelengths higher than 1550 nm can be observed with increasing Sn content. At 1600 nm, the optical responsivity is increased by more than a factor of 10 for the GeSn diode with 4 Sn in comparison to the Ge reference diode. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-29